Small signal stability of washout filter–based power sharing for an inverter‐based microgrid. Issue 2 (1st February 2023) - Yazdanian, Mehrdad; Leitner, Stefan; Fouladi, Ehsan; Mehrizi‐Sani, Ali; Muetze, Annette
Abstract: Different control tasks within a microgrid are usually classified into a hierarchy including zero, primary, secondary, and tertiary control levels. Generally, power sharing lies in the primary control level and utilizes droop control. Droop control causes deviation of voltage and frequency from their nominal values subsequent to load and generation changes in an islanded microgrid. To eliminate these voltage and frequency deviations, a secondary control level, incorporating low‐bandwidth communication links, is usually employed. However, secondary control increases the complexity and cost of the system. A washout filter–based power sharing approach has been proposed that can maintain the nominal values of the voltage and frequency in the primary control level and thereby eliminate the need for secondary control and communication links. This paper further investigates this concept and derives a state‐space small‐signal model of the proposed washout filter–based power controller in a study microgrid to enable systematic design and performance evaluation, for example, stability and parameter selection. The results are compared with those of the same microgrid with conventional droop power controllers. Finally, simulation case studies are conducted in PSCAD/EMTDC tool to validate the results. Abstract : A washout filter–based power sharing approach has been proposed that can maintain the nominal values of the voltage and frequency in the primary control level and thereby eliminate the need for secondary control and communication links. This paper further investigates this concept and derives a state‐space small‐signal model of the proposed washout filter–based power controller in a study microgrid to enable systematic design and performance evaluation, for example, stability and parameter selection. The results are compared with those of the same microgrid with conventional droop power controllers.